Magnon-Induced Nonreciprocity in a Non-Hermitian Cavity Magnonic System - Mei Wang; Gui-Ling Xiao; Duo Zhang; Deng Wei Zhang; Zhao-Yu Sun; Li-Li Zheng (IEEE Photonics Journal, 2023)
Microwave nonreciprocity is in high demand for applications in information processing. Here, we propose an effective approach to realize robust microwave transmission nonreciprocity in a three-mode non-Hermitian cavity magnetic system (CMS). We show that, around the exceptional point, robust microwave nonreciprocity can be achieved within a small detuning range between the cavity and the microwave field. It is fundamentally induced by means of the cavity-magnon interaction and the effective magnon Kerr nonlinearity. Moreover, in the vicinity of the exceptional point, robust microwave transmission nonreciprocity can be realized over an optimal magnetic field range. This greatly improves the operability for obtaining strong microwave nonreciprocity experimentally. This study may stimulate further investigations and applications of the non-Hermitian CMS in structuring high-performance nonreciprocal devices.